Fostering and Sustaining Diverse Literacy Practices in the Early Childhood Classroom: Reviewing the Literature in Three Areas. (November 2017) - Machado, Emily
In this article, I synthesize extant research that documents how teachers foster and sustain children's diverse literacy practices within the early childhood classroom. Framing this review with Bakhtin's heteroglossia, I draw on theoretical and empirical scholarship in the fields of biliteracy, translanguaging, and culturally sustaining pedagogy. Findings are organized into three themes: (1) comparing languages and literacy practices, (2) hybridizing literacy practices, and (3) engaging children's linguistic and cultural repertoires. I conclude with a discussion of implications for researchers and practitioners.